THE EFFECTS OF THIN CAPITALIZATION, COMPANY SIZE, AND PROFITABILITY ON TAX AVOIDANCE - Sartika N Panjaitan; I Gede Made Artha Dharmakarja (Universitas Mercu Buana Yogyakarta, 2026)
Tax avoidance in Indonesia remains widespread, as reflected in the low tax ratio, posing a serious challenge to efforts to optimize state revenue. This study aims to analyze the influence of thin capitalization, company size, and profitability on tax avoidance in the consumer non-cyclicals sector in 2020-2024. The consumer non-cyclical sector plays a strategic role and makes a large contribution to the national economy, but it cannot be separated from indications of tax avoidance practices. This study uses a quantitative approach, employing panel data regression with the Fixed Effects Model (FEM). The sample comprises 40 companies with 200 observations over five years. The results showed that simultaneously, thin capitalization, company size, and profitability have a significant effect on tax avoidance. Partially, thin capitalization and profitability have a significant positive effect on tax avoidance, while company size has a significant negative effect. The results of this study are expected to provide a basis for tax authorities to formulate more proactive, risk-based tax supervision policies.